Assessment of PV technologies outdoor performance and commercial software estimation in hot and dry climates. (15th March 2022) - Othman, Radwa; Hatem, Tarek M.
Abstract: Photovoltaic (PV) technologies have become an essential part of the global effort to compact climate change. While the MENA region, and in particular Egypt, has been one of the main target locations for PV system installations; because of the region's tremendous potential for solar energy and its location on the sunbelt. Yet, a gap in both literature and long-term industrial experience of PV technologies' installation in this particular region calls for investigation. Therefore, this work focuses on two main objectives: first, conducting an evaluation of long-term outdoor performance of three grid-connected photovoltaic systems (i.e. poly-crystalline, mono-crystalline, and thin-film Cadmium Telluride) installed on the same rooftop in Cairo, Egypt, since October 2013. In which, the three systems will be compared in terms of yield, degradation rate, modules efficiency, and temperature power coefficient. The second objective is to compare the performance of commonly-used commercial software packages (i.e. PVSyst, PVSol, and SMA Sunny Design Web) to the output of the three PV systems mentioned above. In terms of degradation, the average yield degradation value was 1.19%/year, 1.17%/year, and 1.67%/year for poly-crystalline, mono-crystallin, and thin-film Cadmium Telluride respectively. For degradation against temperature, the rates were −1.53%/°C/kWp, −1.22%/°C/kWp, and −1.06%/°C/kWp for the three systems respectively. As for software packages estimation, all three software tend to produce a reasonably accurate annual estimation but they become significantly less accurate with the monthly estimation. The annual errors of the three software ranged from −6.99% to +4.65% which is consistent with the literature. However, the monthly error introduced in this study of the three software ranged from −23.71% to +22.22%. The current work lays down the foundation to enhance PV systems' performance in hot and dry climates, as well as, calls for more accurate models for different PV technologies, especially for hot and dry climates. Graphical abstract: Image 1 Highlights: Monitor outdoor performance of different PV systems over 6 years in hot and dry climate. Annual and seasonal system performances are compared to commercial software packages. Software seasonal accuracy is lower than the annual and underestimate thin-film. The degradation rates are 1.19%, 1.17%, 1.67% for pc-Si, mc-Si, and thin-film respectively. The temperature power coefficient (%/°C/kWp ) is highest for pc-Si and least for thin-film.